PK11195, a peripheral benzodiazepine receptor ligand, potentiates cytotoxic action on cholangiocarcinoma cell lines - Pericleous, S.; Mathieson, W.; Middleton, Nicos; McKay, S.; Biswas, A.; Thomas, G.; Spalding, D.; Hutchins, R. (My University, 2011)
Cholangiocarcinoma (CC) is an uncommon disease with a dismal prognosis. Patients with surgically unresectable disease benefi t little from conventional anticancer therapies such as chemotherapy and radiotherapy. 1-(2-chlorophenylN-methylpropyl)-3-isoquinolinecarboxamide (PK11195) is a benzodiazepine receptor ligand which antagonizes Bcl-2 and Bcl-XL function thus preventing the inhibition of apoptosis. Our aim was to determine the effect of adding PK11195 in vitro to commercially available chemotherapy agents on cultured CC cell lines.
Keywords: Cholangiocarcinoma; Chemotherapy